The Era of Antimicrobial Peptides: Use of Hepcidins to Prevent or Treat Bacterial Infections and Iron Disorders - Barroso, C (2021)
The current treatments applied in aquaculture to limit disease dissemination are mostly based on the use of antibiotics, either as prophylactic or therapeutic agents, with vaccines being available for a limited number of fish species and pathogens. Antimicrobial peptides are considered as promising novel substances to be used in aquaculture, due to their antimicrobial and immunomodulatory activities. Hepcidin, the major iron metabolism regulator, is found as a single gene in most mammals, but in certain fish species, including the European sea bass (Dicentrarchus labrax), two different hepcidin types are found, with specialized roles: the single type 1 hepcidin is involved in iron homeostasis trough the regulation of ferroportin, the only known iron exporter; and the various type 2 hepcidins present antimicrobial activity against a number of different pathogens. In this study, we tested the administration of sea bass derived hepcidins in models of infection and iron overload. Administration with hamp2 substantially reduced fish mortalities and bacterial loads, presenting itself as a viable alternative to the use of antibiotics. On the other hand, hamp1 seems to attenuate the effects of iron overload. Further studies are necessary to test the potential protective effects of hamp2 against other pathogens, as well as to understand how hamp2 stimulate the inflammatory responses, leading to an increased fish survival upon infection.